Cervical Epidural and Subarachnoid Catheter Placement in Standing Adult Horses - Hurcombe, Samuel D.; Morris, Tate B.; VanderBroek, Ashley R.; Habecker, Perry; Wulster, Kathryn; Hopster, Klaus (Frontiers in Veterinary Science, 2020)
Horses underwent either cervical epidural space (CES) catheterization or subarachnoid space (SAS) catheterization while restrained in stocks, under deep sedation (detomidine and morphine) and local anesthesia (mepivacaine 2%) block. Catheters were placed under ultrasound-guidance with visualization of the dura, subarachnoid space, and spinal cord between the first (C1) and second (C2) cervical vertebrae. Following sedation and sterile skin preparation, operator 1 placed under ultrasound guidance, a 6- or 8-inch Tuohy needle with the bevel oriented caudally. For CES, a 6-inch Touhy needle was used with the hanging drop technique to detect negative pressure and operator 2 then passed the epidural catheter into the CES. For SAS, following puncture of the dura, CSF was aspirated prior to placement of the epidural catheter. Placement into either CES or SAS was confirmed with plain and contrast radiography. Catheters were wrapped for the duration of the study. Cerebrospinal fluid (CSF) cytology was assessed up to every 24 hours for the study period. Horses were assessed daily for signs of discomfort, neck pain, catheter insertion site swelling or changes in behavior. A complete post-mortem assessment of the spinal tissues was performed at the end of the study period (72 hours). Two horses had CES catheters and 5 horses had SAS catheters placed successfully. All horses tolerated the catheter well for the duration of the study with no signs of discomfort. Ultrasound was essential to assist placement and radiography confirmed anatomical location of the catheters. CSF parameters did not change over the study period (P>0.9). There was evidence of mild meningeal acute inflammation in one horse and hemorrhage in another consistent with mechanical trauma. Placement of an indwelling CES or SAS catheter appears to be safe, technically simple and well tolerated in standing sedated normal horses.